PENDAMPINGAN PENINGKATAN PRODUKSI UNTUK INDUSTRI KREATIF UD SNACK BU ERNIE DESA SUGIHAN LAMONGAN - Latifah, Eny; Sukma, Diniyah; Arifatin, Nanik; Martiwi, Wanala Abdillaika; Abdullah, Rudi (INCIDENTAL : Journal Of Community Service and Empowerment, 2023)
Assistance in the framework of this community service has the aim of helping the creative industry UD Snack Bu Ernie Sugihan Lamongan Village in increasing production and income. The service method is PAR (Participatory Action Research) with observation stages through preliminary research, inculturation, Action Action and Evaluation. The result of the service is the lack of creative industry players who have a computer or laptop so that it is not optimal in uploading creative industry products in the digital marketpalce. The hope is the availability of adequate electronic media so that it is more optimal in utilizing social media and market places available in this digital era. Increased literacy regarding product packaging and marketing, maximizing social media in promotion and sales, and establishing cooperation with partners engaged in the creative industry or trade.